Microbiological Sampling in Total Knee Arthroplasty After Post-Traumatic Osteoarthritis: Rate of Periprosthetic Joint Infection and the Debate Around Sampling Unremarkable Tissue - Felix Erne; Leonard Grünwald; Tina Histing; Philipp Hemmann (Microorganisms, 2025)
Background: Proximal tibial fractures can lead to post-traumatic osteoarthritis (PTOA), and subsequent total knee arthroplasty (TKA) in such patients is associated with elevated complication rates. A two-stage approach, involving the elective removal of osteosynthetic hardware prior to TKA, is recommended. The utility of microbiological sampling from macroscopically unremarkable tissue during TKA implantation remains controversial. Objective: To retrospectively evaluate the rate of periprosthetic joint infection (PJI) following TKA after PTOA and to assess the potential benefit of intraoperative microbiological sampling. The secondary objective was to evaluate the presence of prior colonization in osteosynthetic hardware among the affected cases. Patients and Methods: A retrospective screening of the hospital database was conducted between 2008 and 2022, including only AO/OTA type 41-B and 41-C fractures. Patients were assigned to a sampling group (with microbiological sampling during TKA) or a control group (without sampling). All patients received structured follow-up to assess postoperative complications. Results: A total of 40 patients met the screening criteria. In the sampling group (n = 29), 17.24% required surgical revision, and the rate of PJI was 3.45%. In the control group (n = 11), 18.14% underwent revision surgery, with a PJI rate of 9.09%. The average follow-up period was 4.35 years (range 2–11.6 years). Discussion: TKA in patients with PTOA is associated with a heightened risk of complications. A noteworthy possible correlation between systematic microbiological sampling and reduced PJI incidence was observed. While the small sample size limits definitive conclusions regarding causality, the findings support the potential value of consistent intraoperative sampling.